ucumeropsis mannii seed oil protects against Bisphenol A- induced testicular mitochondrial damages - Patrick Maduabuchi, Aja; Hilary Akobi, Ogwoni; Peter Chinedu, Agu; Ejike Ugbala, Ekpono; Joshua Nonso, Awoke; Oliver Ugochukwu, Ukachi; Obasi Uche, Orji; Boniface Anthony, Ale; Chinonso Peter, Nweke; Esther Ugo, Alum; Darlington C., Chukwu; Christian E., Offor; et al. (Food Science & Nutritution, 2023)
here has been increasing search for the ameliorative properties of seed oils against toxicants. bisphenol A acts as an estrogenic endocrine-disrupting chemical capable of causing male infertility. This study aimed to explore Cucumeropsis mannii seed oil effects against mitochondrial damage in rats using bisphenol A. Forty-eight rats were randomly assigned to six groups (n = 6) of eight rats each and fed the same food and water for 6 weeks. The group A rats were given 1 mL olive oil, while the ones in group B were given bisphenol A at 100 mL/kg body weight via oral route. Group C received C. mannii seed oil 7.5 mL/kg body weight C. mannii seed oil, while group D, group E, and group F were pre-administered bisphenol A at 100 mL/kg body weight, followed by treatment with C. mannii seed oil at 7.5, 5, and 2.5 mL/kg body weight, respectively. Antioxidant enzymes, glutathione, reactive oxygen species, testicular volume, malon- dialdehyde, body weight, and testicular studies were done using standard methods. The results of the bisphenol A-administered group showed a significant decrease in the antioxidant enzymes, glutathione, body weight, and testicular volume with eleva- tion in the levels of reactive oxygen species, malondialdehyde, and testicular indices. BPA + CMSO-treated group showed a significant increase in GPx activity compared with BPA-exposed rats. CMSO treatment significantly increased catalase activity in comparison with that of rats exposed to BPA. Remarkably, C. mannii seed oil and bi- sphenol A co-administration significantly reversed the abnormalities observed in the dysregulated biochemical biomarkers. Our findings suggest that C. mannii seed oil has considerable antioxidant potential which can be explored in therapeutic development against systemic toxicity induced by exposure to bisphenol A. Cucumeropsis mannii seed oil protects against bisphenol A-induced testicular mitochondria damages.